Psychological Factors Motivating the Intention to Utilize Mass Transport Vehicles - Juneman Abraham (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
The field of transportation psychology has yet to develop rapidly in Indonesia. Inner city transportation council members with an educational background in psychology are still quite rare. There is only one professor in transportation psychology. On the other hand, transportation problem increases in both quantity and quality, especially in major cities. One main source of transportation problem in cities is the lack of willingness of people to use mass public transport vehicle, resulting in traffic jams in main roads to other alternative roads. The current theoretical review article aims to show the various psychological variables that are capable of predicting motives and intentions of individuals to use mass public transport vehicle. Such psychological knowledge is expected to contribute as a possible suggestion of an intervention supporting the effort of the government in the development of transportation facilities and infrastructure, transport regulations, and economic policies related to transportation.